Research on the Mechanism of the Influence of Farm Scale on the Environmental Efficiency of Apple Production—Tests Based on a Life Cycle Assessment Perspective - Wenwen Yu; Jin Yu; Xiaonan Chen (Land)
The present study explores the impact of farm scale on environmental efficiency to provide theoretical support and policy reference for the modernization and sustainable development of the apple industry. The study is based on research data from apple farmers in three counties of the Shaanxi and Gansu provinces in 2021. Firstly, the life cycle approach is applied to assess the comprehensive environmental pollution emissions in apple production and to clarify the non-desired outputs. Secondly, the environmental efficiency of apple production is measured using the SBM model, based on which the Tobit model is utilized to explore the impact of operation scale on the environmental efficiency of apple production and its potential mechanism of action. The results of the study show the following: (1) The mean environmental efficiency of the farmers in the sample is 0.278, indicating that the overall environmental efficiency of apple production is low; (2) there is an inverted U-shaped relationship between the scale of operation and the environmental efficiency of apple production, and the results are robust. This analysis was conducted after addressing endogeneity. Thirdly, the study found that the intensity of the adoption of green technology and farmers’ environmental awareness play a significant mediating role in the influence of business scale on the environmental efficiency of apple production. The potential mechanism of the effect of the scale of operation on the environmental efficiency of apple production was also investigated. Consequently, it is recommended to expedite the promotion of moderate-scale orchard operations, to proactively cultivate new management entities, and to enhance the adoption level of green technology and environmental cognition among farmers. These measures are proposed to encourage sustainable and high-quality development in the apple industry.